2013
DOI: 10.5604/12314005.1135314
|View full text |Cite
|
Sign up to set email alerts
|

Model Based Prediction of the Crankshaft Instantaneous Angular Speed Fluctuations

Abstract: The paper presents results of the calculation, based on simplified engine model, aimed on prediction of IAS (Instantaneous Angular Speed) of the crankshaft fluctuations under faulty engine condition. Gas forces were calculated basing on results of in-cylinder pressure measurements which were used as inputs to the dynamic model. Mass forces were calculated basing on technical particulars of the engine Sulzer 3Al 25/30.Measurements of the incylinder pressure was carried out at laboratory stand in Gdynia Maritime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…The Figure (4) shows a series of total loss torque obtained for the gas pedal position α=0,45. From this Figure we notice that the evolution of the total lost torque is proportional to the rotational speed.…”
Section: Total Loss Torque Prediction Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Figure (4) shows a series of total loss torque obtained for the gas pedal position α=0,45. From this Figure we notice that the evolution of the total lost torque is proportional to the rotational speed.…”
Section: Total Loss Torque Prediction Methodsmentioning
confidence: 99%
“…This measured parameter was largely exploited. Various studies have estimated indicated torque and eventually in-cylinder pressure using crankshaft angular speed measures injected in a rigid-body or elastic-body engine model built from the second Newton's law [3,4]. The indicated torque reconstruction from crankshaft speed fluctuations can be achieved with two main approaches, mathematical models and database-based methods like explained in the reference [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The technical condition of an engine exerts direct impact on the course of the working process occurring in the engine cylinders. Consequently it has an impact on fluctuations of the angular velocity of its crankshaft [3,9,10]. Fluctuations of the angular velocity of the crankshaft translate into fluctuations of the angular velocity of the generator rotor.…”
Section: Assumptions Of the Methodsmentioning
confidence: 99%